Pelatihan Pemantapan Sistem Operasi Linux Sebagai Bekal Persiapan Uji Kompetensi Ujian Nasional Tingkat Kejuruan - Agus Perdana Windarto; Anjar Wanto; Mesran Mesran (JPM: Jurnal Pengabdian Masyarakat, 2021)
According to the title of the program, the method of ipteks maintenance that is used is learning and exploring the Linux Operating System. Pelatihan keterampilan ditunjang dengan ceramah, tanya jawab, dan juga langsung praktek di laboratorium komputer. Modul pelatihan diberikan kepada peserta sebagai alat kegiatan praktek di laboratorium. The goal of this program's implementation is to improve the performance of SMK UISU students through the use of word processing applications, as well as to teach SMK UISU students about the Linux Operating System, in order to reduce the gap between SMK UISU student performance and the national average. Based on the results of the evaluation and the lessons learned during the implementation of the P2M program, we can conclude that the program is capable of providing significant and timely benefits to khalayak anak-anak panti asuhan, which has become a khalayak sasaran in the process. Pelatihan like this is a very effective way of providing new knowledge and understanding in the field of information technology in the context of the various learning processes that take place in schools across the country